Trunk control scales as functional predictors for stroke patients - Aguiar, Paula Teixeira de; Rocha, Talitha Nery; Oliveira, Elisandra Silva de (Acta Fisiátrica, 2008)
According to the World Health Organization (WHO), stroke is considered a syndrome with a rapid development of clinical signs of focal or global disturbance of cerebral function, of which origin is possibly vascular and lasting more than 24 hours. In addition to deficits in limb movement, gait, and language, the stroke may also cause impaired control of trunk mobility, which is an important issue. Therefore, the aim of this literature review was to identify, through the use of scales, the association between trunk control impairment and functional disability in hemiparetic patients after a stroke. A literature review was carried out and eight clinical, longitudinal and descriptive articles were selected. All the studies showed a prognostic association between trunk control and functional abilities. Trunk Control Test (TCT), Trunk control items of the Postural Assessment Scale for Stroke Patients (PASS-TC) and Trunk Impairment Scale (TIS) (Fujiwara and Verheyden) were used in the assessments. It was concluded that the clinical evaluation of trunk control, through the use of scales, is an important tool for the prognosis of the functional capacity of hemiparetic patients after a stroke and for the planning of a specific and differentiated treatment of these patients. However, there few studies proved this association, as different scales were used and there was no consensus among authors. Additionally, there is no agreement on the data regarding the evaluation of balance and gait.